2005
DOI: 10.1002/ajim.20224
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary abnormalities associated with occupational exposures at the Savannah River site

Abstract: Pulmonary abnormalities were higher in former SRS workers than that in general population. Asbestos and possibly other exposures were related to pulmonary disease in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
(11 reference statements)
2
9
0
Order By: Relevance
“…The DOE established surveillance programs for several sites around the country under cooperation with universities, labor unions and commercial health care organizations. Results of some of these studies have been described previously in the literature [Stange et al, 1996a[Stange et al, , 2001Dement et al, 2003;Sackett et al, 2004;Welch et al, 2004;Makie et al, 2005;Rodrigues et al, 2008]. This report presents findings of federally mandated screenings for beryllium sensitization among former DOE workers employed at a single weapons assembly plant in the Midwest.…”
Section: Introductionmentioning
confidence: 73%
“…The DOE established surveillance programs for several sites around the country under cooperation with universities, labor unions and commercial health care organizations. Results of some of these studies have been described previously in the literature [Stange et al, 1996a[Stange et al, , 2001Dement et al, 2003;Sackett et al, 2004;Welch et al, 2004;Makie et al, 2005;Rodrigues et al, 2008]. This report presents findings of federally mandated screenings for beryllium sensitization among former DOE workers employed at a single weapons assembly plant in the Midwest.…”
Section: Introductionmentioning
confidence: 73%
“…Deaths due to cancer of the pleura, a disease strongly related to asbestos exposure, were in excess among male SRS workers. The observation is interesting given the findings of the SRS Former Production Worker Health Project, which conducted medical evaluations of 1,368 former SRS workers [Makie et al, 2005]. That study found that pleural abnormalities were more common among male SRS workers than in the general population (OR ¼ 2.4), and were associated with occupational asbestos exposure.…”
Section: Discussionmentioning
confidence: 92%
“…Project, which conducted medical evaluations of 1,368 former SRS workers [Makie et al, 2005]. That study found that pleural abnormalities were more common among male SRS workers than in the general population (OR ¼ 2.4), and were associated with occupational asbestos exposure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While, the primary goal of the NSSP is to screen for potential work‐related medical conditions related to past DOE site employment, the NSSP also addresses non‐occupational conditions. FWP researchers conducted surveillance activities with DOE former workers in relation to specific occupationally related diseases such as hearing loss [Dement et al, ], beryllium sensitization [Welch et al, , ; Newman et al, ; Rodrigues et al, ; Mikulski et al, ], and respiratory disease [Dement et al, , ; Miller et al, , ; Makie et al, ; Newman et al, ; Mikulski et al, ]. However, less is known about the extent to which a former worker program that integrates surveillance for occupational and non‐occupational conditions can contribute to peoples' awareness of non‐work related, often treatable conditions.…”
Section: Introductionmentioning
confidence: 99%